Efficient Intravenous Tumor Targeting Using the αvβ6 Integrin-Selective Precision Virotherapy Ad5NULL-A20 - James A. Davies; Gareth Marlow; Hanni K. Uusi-Kerttula; Gillian Seaton; Luke Piggott; Luned M. Badder; Richard W. E. Clarkson; John D. Chester; Alan L. Parker (Viruses, 2021)
We previously developed a refined, tumor-selective adenovirus, Ad5NULL-A20, harboring tropism ablating mutations in each major capsid protein, to ablate all native means of infection. We incorporated a 20-mer peptide (A20) in the fiber knob for selective infection via αvβ6 integrin, a marker of aggressive epithelial cancers. Methods: To ascertain the selectivity of Ad5NULL-A20 for αvβ6-positive tumor cell lines of pancreatic and breast cancer origin, we performed reporter gene and cell viability assays. Biodistribution of viral vectors in mice harboring xenografts with low, medium, and high αvβ6 levels was quantified by qPCR for viral genomes 48 h post intravenous administration. Results: Ad5NULL-A20 vector transduced cells in an αvβ6-selective manner, whilst cell killing mediated by oncolytic Ad5NULL-A20 was αvβ6-selective. Biodistribution analysis following intravenous administration into mice bearing breast cancer xenografts demonstrated that Ad5NULL-A20 resulted in significantly reduced liver accumulation coupled with increased tumor accumulation compared to Ad5 in all three models, with tumor-to-liver ratios improved as a function of αvβ6 expression. Conclusions: Ad5NULL-A20-based virotherapies efficiently target αvβ6-integrin-positive tumors following intravenous administration, validating the potential of Ad5NULL-A20 for systemic applications, enabling tumor-selective overexpression of virally encoded therapeutic transgenes.